1984
DOI: 10.1136/ard.43.6.783
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age of onset and patient's sex on the prevalence and severity of manifestations of Behcet's syndrome.

Abstract: SUMMARY Eye disease, arthritis, folliculitis, and thrombophlebitis were more common among males, and erythema nodosum among females, in 297 patients with Behqet's syndrome (BS) at their first visit despite an identical disease duration. Younger males and females (age of onset 24 years or less) had a higher prevalence of eye disease and total clinical activity than did the older patients (age of onset 25 years or more). Among the 51 patients followed up for 52 months (SD 7 months) the total clinical activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
176
3
16

Year Published

1989
1989
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(234 citation statements)
references
References 3 publications
32
176
3
16
Order By: Relevance
“…In a hospital-based series, KuralSeyahi et al (7) observed an increased mortality in patients with BD, in particular among young males, which tended to decrease with the passage of time. However, in agreement with our data, 2 other studies reported no increase in mortality in patients with BD (42,43). Turning to morbidity, we looked specifically at inflammatory ocular disease, because this is both a frequent and a potentially serious complication of BD with a significant risk of visual loss (1,2).…”
Section: Seventeen-year Study Of Behçet's Disease In Italysupporting
confidence: 89%
“…In a hospital-based series, KuralSeyahi et al (7) observed an increased mortality in patients with BD, in particular among young males, which tended to decrease with the passage of time. However, in agreement with our data, 2 other studies reported no increase in mortality in patients with BD (42,43). Turning to morbidity, we looked specifically at inflammatory ocular disease, because this is both a frequent and a potentially serious complication of BD with a significant risk of visual loss (1,2).…”
Section: Seventeen-year Study Of Behçet's Disease In Italysupporting
confidence: 89%
“…We have found only 27 reported cases of Behset's syndrome and amyloidosis, which includes our 5 patients. Twentyfive of these patients were men, confirming our previous observation that Behset's disease is generally more severe among men (7). The duration between the first symptoms of Behqet's disease and the emergence of amyloidosis vaned considerably among our 5 patients (Table I); this has also been reported by others (3).…”
Section: Resultssupporting
confidence: 90%
“…The total clinical activity index of Behget's syndrome was calculated for each patient as described previously (7). Briefly, this activity index is a weighted score of only clinical symptoms and signs related to various organ systems, with 0 denoting no involvement.…”
Section: Methodsmentioning
confidence: 99%
“…Seyahi and Yazici for their interest in our work regarding the interplay between BD and pregnancy and for bringing new elements to the discussion. A reduction in BD activity associated with the passage of time has been previously reported (1)(2)(3)(4)(5). Seyahi and Yazici suggest that shorter disease duration might account for the lower frequency of BD flares that we observed in our patients during pregnancy.…”
Section: Replysupporting
confidence: 79%
“…It is well recognized that BD becomes less severe with the passage of time (2). Thus, the inherent disease course in these patients is another factor that might have influenced the smaller number of flares during pregnancies.…”
Section: To the Editormentioning
confidence: 99%